2002
DOI: 10.1182/blood.v99.11.4216
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between glutathione S-transferase M1, T1, and P1 polymorphisms and chronic lymphocytic leukemia

Abstract: Interindividual differences in susceptibility to hematologic malignancies may be mediated in part through polymorphic variability in the bioactivation and detoxification of carcinogens. The glutathione S-transferases (GSTs) have been implicated as susceptibility genes in this context for a number of cancers. The aim of this study was to examine whether polymorphic variation in GSTs confers susceptibility to chronic lymphocytic leukemia (CLL). GSTM1, GSTT1, and GSTP1 genotypes were determined in 138 patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
3
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 6 publications
4
37
3
3
Order By: Relevance
“…A potential etiologic role of the polymorphism has also been suggested for non-Hodgkin's lymphoma in some studies (50)(51)(52)(53). Furthermore, it is noteworthy that GST polymorphisms have been identified as a prognostic factor in pediatric non-Hodgkin's lymphoma (54) and as a risk factor for chronic lymphocytic leukemia (55). The latter association is interesting as several epidemiologic studies have shown that patients with chronic lymphocytic leukemia have an increased risk of smoking-related malignancies such as cancers of the lung, urinary bladder, and larynx (56-58).…”
Section: Discussionmentioning
confidence: 99%
“…A potential etiologic role of the polymorphism has also been suggested for non-Hodgkin's lymphoma in some studies (50)(51)(52)(53). Furthermore, it is noteworthy that GST polymorphisms have been identified as a prognostic factor in pediatric non-Hodgkin's lymphoma (54) and as a risk factor for chronic lymphocytic leukemia (55). The latter association is interesting as several epidemiologic studies have shown that patients with chronic lymphocytic leukemia have an increased risk of smoking-related malignancies such as cancers of the lung, urinary bladder, and larynx (56-58).…”
Section: Discussionmentioning
confidence: 99%
“…GST detoxified agents are, for example, polycyclic aromatic hydrocarbons, which may be found in pesticides 11 . Therefore, individuals with null genotype for GSTM1 and GSTT1 have a higher risk for oxidative stress associated diseases 12,29 , including PD 10,16 . However, there is little research on this matter, and even less on Brazilian individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Yuille et al [30] tested 138 adult B-CLL patients and 280 normal controls to demonstrate a 1.3 times higher frequency of the GSTM1 null genotype in the former group than in the latter (95% CI 5 0.8-1.9).…”
Section: Gstm1 Gstt1mentioning
confidence: 99%
“…Thus, it would be interesting to investigate associations between polymorphous variants of xenobiotic-metabolizing genes and risk of development of other lymphoproliferative diseases. The data concerning B-CLL and NHL susceptibility regarding xenobiotic-metabolizing genes status are limited and sometimes contradictory [26][27][28][29][30][31][32]. There might be gender-specific and subtype-specific associations that require further investigations.…”
Section: Introductionmentioning
confidence: 99%